Gold-catalyzed regio- and stereoselective α-acyloxy-β-alkynylation of ynol ethers - Liu, Yaowen; Han, Chunyu; Shi, Hongwei; Mackenroth, Alexandra; Zhang, Linghua; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (The journal of organic chemistry, 2023)
Enol esters and conjugated enynes are valuable structural motifs for synthetic chemistry and material sciences. Herein, the synthesis of tetra-substituted enol ester 2-iodobenzoate derivatives was achieved in good yields at room temperature through a gold-catalyzed acyloxyalkynylation of sensitive ynol ethers with ethynylbenziodoxolones (EBXs), the latter acting as bifunctional reactants. The conversion is highly regioselective with a broad substrate scope. Mechanistically, an Au(III) species is the key intermediate of an Au(I)/Au(III) redox cycle. The reaction is synthetically useful and can easily be scaled up to gram scale.